ANALISIS KELAYAKAN FINANSIAL USAHA PEMBIBITAN LADA DI DESA SUKADANA BARU KECAMATAN MARGA TIGA KABUPATEN LAMPUNG TIMUR - M Safrizal Anwar; Ali Ibrahim Hasyim; Muhammad Irfan Affandi (Lampung University, 2018)
This research aims to analyze financial feasibility of pepper nursery business and feasibility sensitivity. The research was conducted in Sukadana Baru Village, Marga Tiga District, Lampung Timur Regency in March to April 2017. Respondents are six pepper nursery farmers. Note that the used research method is the case study where the quantitative analyses are utilized as the data analysis using Internal Rate of Return (IRR), Net Present Value (NPV), Payback Periode (PP), Gross Benefit Cost Ratio (Gross B/C), and Net Benefit Cost Ratio (Net B/C). The results showed that (1) the pepper nursery business in Sukadana Baru Village, Marga Tiga District, Lampung Timur Regency is financially feasible to be expanded, (2) the sensitivity analysis shows that this business is still feasible and profitable toward the decreasing production and selling price of pepper nursery as well as the increasing costs of manure and NPK fertilizer.. Key words : financial, feasibility, pepper nursery, sensitivity